Solid Dispersion: Methods and Polymers to increase the solubility of poorly soluble drugs - Ladan Akbarpour Nikghalb, Gurinder Singh, Gaurav Singh and Kimia Fazaeli Kahkeshan (Journal of Applied Pharmaceutical Science)
The solubility behaviour of drugs remains one of the most exigent aspects in formulation development. These days, the number of new chemical entities has dramatically increased having hiccups of poor solubility and poor permeability. Solid dispersion as a dosage form has been established a superior option for the drugs having poor aqueous solubility. Solid dispersions in water-soluble carriers have engrossed considerable interest as a means of improving the dissolution rate and bioavailability of hydrophobic drugs. Although solid dispersions have tremendous potential for improving drug solubility and only a few marketed products using this approach. There are various methods available to improve the solubility of the new drug in which solid dispersion emerged promising. A Solid dispersion generally composed of two components- the drug and the polymer matrix. Numerous methods are existing to prepare the solid dispersions such as melting method, solvent evaporation method, fusion method, kneading method, melting method, spray drying method, co-grinding method, lyophilization technique, hot melt extrusion, melt agglomeration, supercritical fluid (SCF) technology etc. A variety of hydrophilic carriers have been investigated for enhancement of dissolution characteristics and bioavailability of poorly aqueous-soluble drugs. In this review an endeavour is made to discuss about the comprehensive methods of preparation and numerous carriers are used for solid dispersions.
Keywords: Dissolution,Solid Dispersion,Solubility,Cellulose Derivatives,Polyethylene glycol.